Economics for business - Mitchelson, Peter; Mann, Andrew (South Melbourne : Nelson, 1995)
This book presents about Microeconomics and Macroeconomics.
Keywords: Australia; Economics; Economics; Australia -- Economic conditions; Australia -- Economic policy; Australia -- Economic policy